A Nanocomposite Shield Constructed for Protection Against the Harmful Effects of Dental X-Rays - Simel Ayyıldız; Elif Hilal Soylu; Jülide Özen; Semra İde; Kıvanç Kamburoğlu (Tehran University of Medical Sciences, 2016)
Objectives: This study aimed to compare a number of new nanocomposites capable of pro- tecting the jaw from ionizing radiation. Materials and Methods: Four different types of nano-powders [Ti, Zr (IV) oxide, Ag and Co] were mixed in a polymer matrix to create nano-composites with doping values of 8% in weight. Small-angle X-ray scattering (SAXS) analysis was performed using a HECUS- SAXS system with 50 kV- 50 mA. Co nano-composites (Co-pnm) yielded the most prom- ising values of the 4 nanocomposites tested in terms of x-ray absorption. Thus, 4x2 cm Co- pnm samples of different thicknesses (0.20, 0.50, 0.57 and 0.60 cm) were prepared, and SAXS analysis was performed in order to assess the effects of material thickness on x-ray absorption. An experimental multi part shield was constructed from Co-pnm around tooth #36 to test the effect of nanomaterial on the image quality under X-ray beam. Results: Logarithmic distributions of the transmitted intensity values (I) showed that 0.20 cm Co-pnm had the highest transmission value (16.05) followed by 0.50 cm Co-pnm (15.44), 0.57 cm Co-pnm (15.07) and 0.60 cm Co-pnm (15.06). The 0.2 cm Co-pnm had an effective radius of the nano-aggregation value (77.44 Å) lower than that of the other thick- nesses (0.50, 0.57 and 0.60 cm) of Co-pnm, which had similar values ranging from 66.22-66.34 Å. The 0.50 cm Co-pnm had the lowest Dmax value of the different thicknesses of Co- pnm tested. Conclusion: Co nanocomposite can be used as a protection shield for the harmful effects of dental X-ray.